The Relationship between Assertive Behavior and Stress Level in Students of SMAN 1 Ngawen - Susi, Carisa (Penerbit Hellow Pustaka, 2025)
This research is motivated by the differences between western and eastern cultures regarding how to handle stress, some argue that assertive behavior can be an alternative for reducing stress while there are also those who say that western culture has not yet been implemented in eastern countries, especially Javanese people who have an attitude of pakewuh and harmony. The aim of this research is to determine the relationship between assertive behavior and stress levels. In this research, the method used was quantitative with a correlation research type, the population in this research was 288 students. The sample in this study was taken as 25% of the total population so that the sample used was 72 students which was determined using proportional random sampling technique. The data collection technique used was a Likert scale questionnaire with Google Form. The results of the product moment correlation obtained an rcount correlation value of -0.576 with an rtable value at 5% significance of 0.229, therefore rcount -0.576 > rtable 0.229. So it can be concluded that there is a significant relationship with a moderate correlation coefficient in the results of this study. The limitation of this research is that it only focuses on finding a relationship between two variables, namely assertive behavior and stress levels because the researcher only focuses on a few factors so there is not enough depth regarding other factors